Penerapan Metode Pembelajaran Melalui Media WhatsApp Selama Pandemi COVID-19 di RA Al-Qodir - Al-Qudus Nofiandri Eko Sucipto Dwijo; Sri Indarwati; Citra Amaliyah Saraswita Suwandini; Siti Mustainah (JECED : Journal of Early Childhood Education and Development, 2020)
This study aims to determine the online learning methods used by RA AL Qodir teachers during the COVID-19 pandemic and the media used to communicate with children during the distance learning process. This research is a descriptive analytic type of research with a qualitative.-phenomenological approach. The subjects of thid study were the Head of RA, teachers and students. The research instruments used were interviews, documentation and observation of the research subject. The results of this study are that teachers must be able to use learning methods that are appropriate to the situation and conditions. The learning methods used at RA AL Qodir during the COVID-19 pandemic were playing methods, chatting, demonstrations,telling stories and assigning assignments. Distance learning is no longer an obstacle to the stopping of the teaching and learning process because it has provided facilities and opportunities in various conditions, including the COVID-19 pandemic. The WhatsApp application is a learning medium to communicate and discuss with each other. Teachers who are creative and discuss with each other. Teachers who are creative and innovatice in presenting learning materials have an effect on children’s learning outcomes and children’s learning interests